Giant Cell Fibroma in a Paediatric Patient: A Rare Case Report - Veera Kishore Kumar Reddy; Naveen Kumar; Prashant Battepati; Lalitha Samyuktha; Swapna Priya Nanga (Hindawi Limited, 2015)
Giant cell fibroma is a form of fibrous tumour affecting the oral mucosa. Its occurrence is relatively rare in paediatric patients. Clinically it is presented as a painless, sessile, or pedunculated growth which is usually confused with other fibrous lesions like irritation fibromas. Here we are presenting a case where a seven-year-old male patient reported with a painless nodular growth in relation to lingual surface of 41 and 42. Considering the size and location of the lesion, excisional biopsy was performed and sent for histopathological analysis which confirmed the lesion as giant cell fibroma.